PEMETAAN KONDISI FISIK JARINGAN IRIGASI DESA RASI RAYA KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA BERBASIS SISTEM INFORMASI GEOGRAFIS - Stevano F. X. Hariawan; David P. Rumambi; Sandra E. Pakasi (Universitas Sam Ratulangi, 2019)
ABTRACTThe Lahendong Irrigation Network is located in Rasi Raya Village RatahanSubdistrict Southeast Minahasa Regency, which was established in 1971. In December 2013,damage to buildings and channels in the irrigation network. This research aims to make amap of physical conditions in the village of Rasi Raya, Ratahan District, Southeast MinahasaRegency, based on geographic information systems. This research was conducted in July2019-October 2019. The method is used in this research is imagery by using analysis fromGIS Software and measurements of the field. Lahendong Irrigation Network is geographicallyat 0°59'19.34